Pengaruh Kompetensi dan Komitmen Tenaga Medis Terhadap Kepuasan Serta Implikasinya Terhadap Kepercayaan Pasien di Instalasi Rawat Jalan Rumah Sakit Umum Rama Hadi Purwakarta - Nurdiansyah, Robby; Saepudin, Didin; Rulia, Rulia; Rahmiyati, Ayu Laili; Paramarta , Vip (Jurnal Locus Penelitian dan Pengabdian, 2025)
Health services are an important part of the government's efforts to fulfill people's rights to health. At RSU Rama Hadi Purwakarta, patient complaints arose related to late visitations, lack of communication, and uncertain service schedules, which reflected problems in the competence and commitment of medical personnel. This has a direct effect on patient satisfaction and trust in health care institutions. This study aims to analyze the influence of competence and commitment of medical personnel on patient satisfaction and its impact on patient trust in the Outpatient Installation of Rama Hadi Purwakarta Hospital. The method used is a descriptive quantitative approach with an explanatory design. Primary data was collected through the distribution of questionnaires to 172 outpatients. The independent variable is the competence and commitment of medical personnel, the mediating variable is patient satisfaction, and the dependent variable is patient trust. Data analysis was carried out using the path analysis method to measure the relationship between variables. The results showed that the competence of medical personnel had a positive and significant effect on patient satisfaction (? = 0.193; p = 0.003), while the commitment of medical personnel had the strongest influence (? = 0.464; p = 0.000). Patient satisfaction also significantly affected patient confidence (? = 0.296; p = 0.000). Competency (? = 0.179; p = 0.001) and commitment (? = 0.250; p = 0.000) had a direct effect on patient confidence. Indirectly, competence and commitment affect trust through satisfaction. This study suggests increasing the competence and commitment of medical personnel as a strategy to increase patient satisfaction and trust.